Reseñas de cuentos aparecidas en los diarios ABC (ABC Cultural) y El País (Babelia) 1996-1999 - Linares Valcárcel, Francisco; Romero López, Dolores (Signa: Revista de la Asociación Española de Semiótica, 2021)
-